2021
DOI: 10.5334/labphon.280
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of cumulativity in sound symbolism: Experimental studies of Pokémonastics with English speakers

Abstract: There has been a dramatic rise of interest in sound symbolism, systematic associations between sounds and meanings. Despite this, one aspect that is still markedly under-explored is its cumulative nature, i.e., when there are two or more sounds with the same symbolic meaning, whether these effects add up or not. These questions are important to address, since they bear on the general question of how speakers take into account multiple sources of evidence when they make linguistic decisions. Inspired by an accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
(181 reference statements)
0
12
0
Order By: Relevance
“…Recent work has also demonstrated a "longer-is-stronger" effect, such that larger Pokémon characters were attributed names with greater mora counts (i.e., long vowels; Kawahara et al, 2018Kawahara et al, , 2020Kawahara, 2020). Following up from these findings, Kawahara and Kumagai (2019) showed how both native Japanese and English speakers attributed names containing greater mora counts to evolved (i.e., larger) characters, compared to their un-evolved (smaller) forms (see also Kawahara and Breiss, 2021). It has been suggested this effect is comparable to quantitative iconicity in grammar (Haiman, 1980; see discussion in Kawahara et al, 2018;Kawahara and Breiss, 2021).…”
Section: Mora Countmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent work has also demonstrated a "longer-is-stronger" effect, such that larger Pokémon characters were attributed names with greater mora counts (i.e., long vowels; Kawahara et al, 2018Kawahara et al, , 2020Kawahara, 2020). Following up from these findings, Kawahara and Kumagai (2019) showed how both native Japanese and English speakers attributed names containing greater mora counts to evolved (i.e., larger) characters, compared to their un-evolved (smaller) forms (see also Kawahara and Breiss, 2021). It has been suggested this effect is comparable to quantitative iconicity in grammar (Haiman, 1980; see discussion in Kawahara et al, 2018;Kawahara and Breiss, 2021).…”
Section: Mora Countmentioning
confidence: 90%
“…Following up from these findings, Kawahara and Kumagai (2019) showed how both native Japanese and English speakers attributed names containing greater mora counts to evolved (i.e., larger) characters, compared to their un-evolved (smaller) forms (see also Kawahara and Breiss, 2021). It has been suggested this effect is comparable to quantitative iconicity in grammar (Haiman, 1980; see discussion in Kawahara et al, 2018;Kawahara and Breiss, 2021). If so, perception of extended vowel production (with greater mora count) more readily affords iconicity, compared to shorter productions.…”
Section: Mora Countmentioning
confidence: 92%
“…Durvasula & Liter (2020) also used an AGL task to examine multiple concurrent phonological generalizations learned over representations of different grain-sizes, and also found results that are compatible with linear cumulativity. Moving beyond the domain of linguist-created languages, Kawahara & Breiss (2021) examined cumulativity in sound symbolism, and found that participants combined multiple phonological cues to the same sound-symbolic quality in a cumulative manner in the domain of Pokémon names (see also Kawahara & Moore 2021;Kawahara 2021). Pizzo (2015) found that English-speaking participants judged words which violated English syllablemargin phonotactics in one location, ex.…”
Section: Evidence For Cumulativity Of Violationsmentioning
confidence: 99%
“…Kawahara and Kumagai (2019b) confirmed the productivity of these associations by an experimental study 1 However, Pokémonastics, which analyzes made-up names of fictional characters, is not meant to replace the studies of sound symbolism using real words; it is instead meant to complement other related studies on sound symbolism. See Kawahara and Breiss (2021) for some extended discussion on this point. 2 A reviewer raised an interesting challenge related to this thesis-the set of denotations that needs to be expressed by a language in the real world is much larger than this N, and it would be reasonable to conjecture that the expressive power that is required in such situations may not allow sound symbolism to persist as strongly, at least compared to the Pokémon universe, given that the number of phonemic contrasts is limited (cf.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While Japanese is actively studied via experimentation within the Pokémonastics paradigm (e.g., Kumagai, 2019a,b, 2021;Kumagai and Kawahara, 2019;Kawahara, 2020b;Kawahara et al, 2020), we are yet to gather more data from other languages in order to more thoroughly address the cross-linguistic similarities and differences in sound symbolism. A few studies have gathered experimental data from native speakers of English and Brazilian Portuguese regarding sound symbolism signaling a pre-vs. post-evolution distinction, where post-evolution characters are generally larger, heavier and stronger (Godoy et al, 2020;Kawahara and Breiss, 2021;Kawahara and Moore, 2021). However, other than these, experimental studies on languages other than Japanese are limited.…”
Section: Theoretical Backgroundmentioning
confidence: 99%